The Influence of Flash Sale and Shopee Live on Impulsive Buying Behavior in Marketing Management Students - Zuchdiawati Luthfi Utami (MAMEN: Jurnal Manajemen, 2024)
This research aims to find out how much influence Flash sale and Shopee Live features have on impulsive buying behavior among D4 Marketing Management students at Yogyakarta State University who belong to Generation Z and are frequently shopping online via Shopee application. This quantitative research used a sample of 93 students taken using a purposive sampling technique and a questionnaire and was analyzed using the SPSS version 25 program. The results of this research show the multiple linear regression equation Y = (5.978) + 0.528X1 + 0.311X2, which means the Flash sale feature and Shopee Live simultaneously have a significant influence of 26.9% (Rsquare = 0.269, α < 0.05) on impulsive buying behavior in students. Partially, only the Flash sale feature has a significant influence on impulsive buying behavior (tcount 3.512 > ttable 1.990). This is because Flash sales provide limited offers with large enough discounts to encourage the desire to take advantage of the opportunity before the product is sold out or the offer ends. Meanwhile, Shopee Live (tcount 1.773 < ttable 1.990) only helps in seeing product quality live so not all students feel motivated to buy products through this feature.